The influence of mfp-implant on tissue pertinent changes of wistar rattus-rattus - ., Widjijono (Indonesian Journal of Pharmacy, 2010)
Fluoride  for  caries  prevention  if  consumes  for  a  long  period,  it  is sometimes  made  bored.  Normally, fluoride intake is uncontrolled and cause fluorosis.  Alternatively, implant fluor becomes the controlled method.  The study was  aimed  to  determine  the  influence  of  MFP-implant  on  tissue  pertinent changes  of  Wistar  Rattus-rattus.  The research subjects were Rattus-rattus mother of 20 rats (2 days pregnant).  Twenty  rats  were  divided  into  4  groups, namely  control  (K),  implant  P1,  implant  P2  and  implant  P3.  Subcutaneous implantation was done on rat back.  On the 8th day, euthanasia was done. Excission  was  done  surround  the  implant  tissue,  then  blocked  and  fixed  by formalin  buffer.  The specimen was cut along the implant tissue were examined by light microscope.  The data were analyzed by descriptive statistic.  The result showed that the incision was cured on the 5th – 7th day.  Tissue pertinent changes determination showed that there was lipid cell infiltration and relatively thicker of tissue on implant P3 and.  There was not any inflammation cell infiltrated and fibrous tissue. In conclusion, the infiltration of lipid cell on implant P3. The implant P2 was fulfilled the requirement of implant devices.Key words: MFP-implant, pertinent changes, rat